Statistics as a Tool for Market Research and Consumer Behavior Analysis - Bohara, Shiv Raj (KVM Research Journal, 2025)
Statistics plays a vital role in market research and consumer behavior analysis, providing businesses with the tools to make informed decisions. By collecting, analyzing, and interpreting numerical data, organizations can identify market trends, understand consumer preferences, and predict future buying patterns. This study examines the application of statistical methods such as surveys, sampling, regression analysis, and descriptive statistics in understanding consumer behavior. It highlights how statistical insights help businesses segment their markets, develop targeted marketing strategies, and optimize product offerings. Moreover, the research explores the challenges of data accuracy, sample representation, and interpretation of results. The findings indicate that effective use of statistics enables businesses to minimize risks, improve customer satisfaction, and gain a competitive advantage in dynamic markets.